The lady with the yellow umbrella a story based on Fernando Amorsolo's painting Sunday morning going to town - Flores, Lin Acacio; Amorsolo, Fernando C. 1892-1972.; Flores, Lisa. ([Makati City] Ayala Foundation, 2004)
Tonio is torn between his duty to help his family work on the farm and his eagerness to go back to school.
Keywords: Rice farmers -- Philippines -- Juvenile fiction; Conduct of life -- Juvenile fiction; Philippine fiction (English)